2020
DOI: 10.1111/1365-2656.13383
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of predator‐induced behavioural plasticity on the temperature dependence of predator–prey activity and population dynamics

Abstract: Predation is a key ecological interaction affecting populations and communities. Climate warming can modify this interaction both directly by the kinetic effects of temperature on biological rates and indirectly through integrated behavioural and physiological responses of the predators and prey. Temperature dependence of predation rates can further be altered by predator‐induced plasticity of prey locomotor activity, but empirical data about this effect are lacking. We propose a general framework to understan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 85 publications
1
16
0
Order By: Relevance
“…Intrapopulation variation in astaxanthin expression is likely affected by factors such as heterogeneities in the light and resource environment (Cieri & Stearns, 1999 ), as well as predation risk by planktivorous fish. Our results are consistent with stickleback, and the predation risk they present, acting as agents of plasticity (Gvoždík & Boukal, 2021 ), and substantially lowering individual astaxanthin expression. It is unclear why stickleback might cause bigger differences among individuals at low content of astaxanthin expression (i.e., when predation risk is presumably the highest).…”
Section: Discussionsupporting
confidence: 88%
“…Intrapopulation variation in astaxanthin expression is likely affected by factors such as heterogeneities in the light and resource environment (Cieri & Stearns, 1999 ), as well as predation risk by planktivorous fish. Our results are consistent with stickleback, and the predation risk they present, acting as agents of plasticity (Gvoždík & Boukal, 2021 ), and substantially lowering individual astaxanthin expression. It is unclear why stickleback might cause bigger differences among individuals at low content of astaxanthin expression (i.e., when predation risk is presumably the highest).…”
Section: Discussionsupporting
confidence: 88%
“…Predator–prey interactions are a central theme to the practice of biological control of insect pests (Laws, 2017) and determine the effectiveness of biological control programs as well as the stability of ecosystem dynamics (Gvoždík & Boukal, 2021). Several attributes determine the success of a predator as a biological control agent, including the predator's feeding response to changes in prey density (Fernández‐Arhex & Corley, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…translating to faster walking speed, shorter host handling time) and behavior (e.g., activity versus quiescence) (Abram et al, 2015;Augustin et al, 2020;Boukal et al, 2019;Moiroux et al, 2016). Species-specific differences in thermal tolerance will yield more complex outcomes at community than at individual level (Boukal et al, 2019;Gilman et al, 2010;Gvoždík & Boukal, 2021;Outreman et al, 2018). In an exemplary experiment, Davis et al (1998b) showed that the competitive outcome between three Drosophila species was driven by temperature, but that the addition of a competing species altered the focal species' thermal optima.…”
Section: Discussionmentioning
confidence: 99%
“…Behaviour is a highly plastic trait and can continuously adapt to match environmental conditions. Temperature affects many components of parasitic or predatory behaviour such as defensive behaviour, host or prey-encounter, attack rates and feeding rates (Gvoždík and Boukal, 2021;Lemoine et al, 2014;Moiroux et al, 2016). Changes in thermal conditions were also found to alter host-selection behaviour, and sex ratio of eggs laid by parasitoids (Moiroux et al, 2015(Moiroux et al, , 2014.…”
Section: Phenotypic Plasticity In Response To Thermal Fluctuations An...mentioning
confidence: 99%
See 1 more Smart Citation